Clinical factors associated with positive corneal culture in suspected microbial keratitis. Issue 5 (October 2022) - Green, Matthew; Zhang, Susan; Nadivulath, Thomas; Apel, Andrew; Stapleton, Fiona
Abstract: Aims: Determine demographic and clinical characteristics associated with positive culture in suspected microbial keratitis. Methods: Retrospective audit of patients that had corneal scrapings between October 1999-September 2004 at Princess Alexandra Hospital. Clinical information was gathered from medical records, smear and culture results from the local microbiology database. Univariate and multivariate analyses of variables associated with positive cultures and calculation of population attributable risk percentage (PAR). Results: Univariate analysis showed that positive cultures were associated with patients over 60 years (81% vs 55%; p < 0.001), presenting visual acuity (VA) of 6/24 or worse (74% vs 57%; p = 0.012) or contact lens-related keratitis (CLK 77% vs 62%; p = 0.08). Analysis of patients' clinical presentation showed that positive culture was associated with a central epithelial defect (74% vs 57%; p = 0.012), anterior chamber reaction of 2 + cells or worse (73% vs 56%; p = 0.03), an epithelial defect of 2 mm or more in diameter (71% vs 50%; p = 0.006) or no prior treatment with antibiotics (68% vs 56%; p = 0.053). Multivariate analysis showed the independent variables associated with positive cultures were VA of 6/24 or worse on presentation, contact lens-related keratitis, age greater than 60 years, an anterior chamber reaction of 2 + cells or worse and no prior treatment with antibiotics. The factor with the highest attributable risk (PAR%) for a positive corneal scraping was VA of 6/24 or worse on presentation (21%). Conclusions: In this series positive cultures were associated with poor presenting VA contact lens keratitis (CLK), older age, anterior chamber reaction and no prior treatment with antibiotics.